DC motor position control for pulley axial movement of an electromechanical dual acting pulley (EMDAP) CVT system - Supriyo, Bambang; Tawi, Kamarul Baharin; Jamaluddin, Hishamuddin; Ariyono, Sugeng (2006)
Currently hydraulic system has been used for changing transmission ratio of metal pushing V-belt Continuously Variable Transmission (CVT) with single acting pulley system. This paper introduces an alternative way of changing transmission ratio using an electromechanical actuator applied to dual acting pulley CVT system. This new system introduces two DC servomotors as actuators and power screw mechanisms as a means of shifting movable pulleys axially along transmission shafts. The primary motor is responsible for changing transmission ratio, while the secondary one is for preventing the metal belt from slipping. Since the methods of controlling these two motors are similar, this paper only discusses the primary part. Fuzzy PID control scheme is proposed for the DC servomotor position control. This controller drives the servomotor to regulate the axial movement of two movable pulley sheaves to shift the metal belt placed between the sheaves, and change the belt-pulley contact radius. Changing this contact radius means changing the transmission ratio. The fuzzy logic controller is used to improve the performance of the conventional PID considerably. Computer simulation results are presented to demonstrate the effectiveness of the proposed fuzzy PID controller as compared to that of the conventional fixed gain PID controller.